Իրակություններ. դրանց գեղարվեստական դրսևորումն ու թարգմանությունը (ըստ դիքենսյան տեքստերի) - Լուսինե Ավետիսյան (ՀՀ ԳԱԱ հրատ.)
Realia as a unique manifestation of the national culture are numerous and refer to various spheres of the given ethnic community- housing, mythological beliefs, dishes, religions, ceremonial traditions, administration, science, technology and so on. It should be noted that realia as material manifestation of the cultural life of the national identity, first have a nominative and then a metaphoric meaning. For example, pudding is a realis, which is often met in Dickens’s prose and by saying pudding its nominative meaning is perceived first of all as a dish. But in combination with other words and in certain contexts this word has a metaphoric meaning as pudding face — broad, plump face, pudding head - rude, stupid person.
Keywords: Language and Literature